ANALISIS EFEKTIVITAS BIDANG KEBERSIHAN DINAS CIPTA KARYA DAN TATA RUANG KOTA DALAM PENGELOLAAN SAMPAH DI KOTA SALATIGA - Fitria Handayani Handayani; Titik Djumiarti; Rihandoyo Rihandoyo (Journal of Public Policy and Management Review, 2014)
Waste management service is one of the government activity. But, The Hygiene Departement of Dinas Cipta Karya dan Tata Ruang as the provider have not been able to run the waste management service in accordance with the Salatiga citizen need. The question is: What are the problems that Salatiga Government face to reach the organizational effectiveness? This study aims to describe the effectiveness of The Hygiene Departement of Dinas Cipta Karya dan Tata Ruang in waste management service in Salatiga with the problems to reach the organizational effectiveness. This research uses descriptive study with a qualitative approach. The waste management study is important to do to reach the effectiveness of The Hygiene Department of Dinas Cipta Karya dan Tata Ruang in waste management service in Salatiga. The result shows that there are some aspects to be improved: the work specialization, organizational structure, leadership, budget, facilities, and the citizen participation.